Pengaruh Kinerja Aparatur Terhadap Kualitas Pelayanan Pembuatan Kartu Keluarga di Kecamatan Tambun Utara Kabupaten Bekasi - Rachman, Muhammad Widigdo; Kurniansyah, Dadan; Ramdani, Rachmat; Hapsari, Rian (Institut Pemerintahan Dalam Negeri, 2021)
This study aims to determine the effect of apparatus performance on the service quality of making family cards in Tambun Utara district, Bekasi district. This research is a quantitative research through survey method with correlation regression data analysis technique. Using the Performance questionnaire instrument to measure the performance of the apparatus includes 4 aspects, namely: quality, quantity, use of time, cooperation and the service quality questionnaire covers 5 aspects, namely: physical form (responsiable), reliability (reability), responsiveness (responsiviness), assurance (assurance. ) and empathy (emphaty). The sample consisted of 122 family heads who took care of making family cards in North Tambun District in 2019-2010. The results showed that there is a significant influence between the performance of the apparatus on the quality of service for making family cards in Tambun Utara District, Bekasi Regency, which is equal to 52.8%, the remaining 47.2% is influenced by other factors outside the performance of the apparatus. Based on the results of the above research, it is concluded that there is a strong influence between the performance of the apparatus on the quality of service for making family cards in Tambun Utara District, Bekasi Regency.